Non-Steroidal FXR Agonistic Dimeric 2-Methyl-4-(1-glycerol)furan with Lipid-Lowering Activities from Marine-Derived Nocardiopsis sp. ZSN1 - Yongjun Jiang; Zhen Lei; Jiebin Fang; Yanping Wu; Chengpeng Sun (Marine Drugs)
Five novel 2-methyl-4-(1-glycerol)furan (MGF) dimers, namely nocardifuran A (1), 13-acetyl-nocardifuran A (2), 15-epi-nocardifuran A (3), nocardifuran B (4), and nocardifuran C (5), were isolated from the Gause liquid fermentation of the marine-derived Nocardiopsis sp. ZSN1. Their structures were elucidated through HRESIMS, 1D and 2D NMR spectroscopic data analysis, and ECD calculations. Compounds 1–4 were identified as derivatives of MGF with its rearrangement of furan or pyran derivatives, while compound 5 was identified as the derivative of MGF with an indole derivative. These MGF dimers, representing a new structural class, were isolated from a marine microorganism for the first time, thereby enhancing chemical diversity. Screening for farnesoid X receptor (FXR) agonistic activity revealed that MGF dimers could activate FXR. Furthermore, bioactivity evaluations demonstrated that these types of compounds exhibited lipid-lowering activity with lower cytotoxicity in vitro. Consequently, our findings not only contribute to the chemical diversity of marine-derived MGF-type natural products but also offer potential insights into the development of MGF dimers as lead compounds for FXR agonists in the dysregulation of hepatic lipid metabolism.